EXPERT SYSTEM FOR DIAGNOSING DIGESTIVE DISEASES IN HUMANS USING WEB-BASED ANALYTICAL HIERARCHY PROCESS AND CERTAINTY FACTOR METHODS - Hasan, Ibnu; Widhiani, Pahla; Sokid, Sokid; Achyar , Tedy (INTI TALAFA, 2025)
Diseases of the gastrointestinal tract are a serious health problem that is the sixth leading cause of death in the world according to WHO (World Health Organization). Digestive diseases are one of the common health problems and often require proper diagnosis for effective treatment. This research aims to develop a web-based expert system capable of diagnosing digestive diseases in humans using the Analytical Hierarchy Process (AHP) and Certainty Factor (CF) methods. The AHP method is used to measure and compare the level of importance of various symptoms, while the CF method is used to calculate the level of certainty of the diagnosis given. The system has 5 diseases with each description and treatment and 25 symptoms. In system testing conducted by researchers, the results of the diagnosis of GERD disease were 51.4%, Dysmenia was 48.2% and Hemorrhoids 27.5%. The test results obtained the same results as the manual calculation by the researcher. Based on the results of system and manual testing, this expert system for diagnosing digestive diseases using the Analytical Hierarchy Process and Certainty Factor methods has succeeded as expected. So that this system can be used by the public and medical personnel who deal with digestive diseases. Keywords: Expert System, Diagnosis, Digestive Diseases, Analytical Hierarchy Process, Certainty Factor